CEMENTIDE: A Creativity Enhanced Model for Effective Integration and Technology Implementation in Developing Economies - Syed Z. Arshad; Javaid R. Laghari (JISR Management and Social Sciences & Economics, 2006)
This paper introduces the CEMENTIDE (Creativity Enhanced Model for Effective Integration and Technology Implementation in Developing Economies) framework. The concept presented in this paper is part of a larger research thesis and contributes to the ideas on creativity through messaging and communication technologies in the context of developing economies.